Epidemiology of functional dyspepsia: a global perspective - Mahadeva, S.; Goh, K.L. (2006)
Dyspepsia refers to group of upper gastrointestinal symptoms that occur commonly in adults. Dyspepsia is known to result from organic causes, but the majority of patients suffer from non-ulcer or functional dyspepsia. Epidemiological data from population-based studies of various geographical locations have been reviewed, as they provide more realistic information. Population-based studies on true functional dyspepsia (FD) are few, due to the logistic difficulties of excluding structural disease in large numbers of people. Globally, the prevalence of uninvestigated dyspepsia (UD) varies between 7%-45%, depending on definition used and geographical location, whilst the prevalence of FD has been noted to vary between 11%-29.2%. Risk factors for FD have been shown to include females and underlying psychological disturbances, whilst environmental/ lifestyle habits such as poor socio-economic status, smoking, increased caffeine intake and ingestion of non-steroidal anti-inflammatory drugs appear to be more relevant to UD. It is clear that dyspepsia and FD in particular are common conditions globally, affecting most populations, regardless of location.